Usefulness of implementing the OHIP‐14 questionnaire to assess the impact of xerostomia and hyposalivation on quality of life in patients with primary Sjögren's syndrome. (30th September 2022) - Serrano, Julia; López‐Pintor, Rosa María; Fernández‐Castro, Mónica; Ramírez, Lucía; Sanz, Mariano; López, Javier; Blázquez, María Ángeles; González, Jorge Juan; Hernández, Gonzalo; ,
Abstract: Background: The aim of this study is to analyze if the results of the Oral Health Impact Profile‐14 questionnaire (OHIP‐14) in patients with primary Sjögren's syndrome (pSS) are correlated with salivary flow and level of xerostomia. Methods: This observational cross‐sectional study was conducted in 61 patients (60 women, one man, mean age 57.64 [13.52]) diagnosed of pSS according to the American‐European Criteria (2002). After recording demographic, medical and dental data (decayed‐missing‐filled teeth index [DMFT]), unstimulated (UWS) and stimulated (SWS) salivary flows were collected. Subsequently, UWS flow was categorized into two groups (<0.1 ml/min and ≥0.1 ml/min) and SWS into three groups (<0.1 ml/min, 0.1–0.7 ml/min and >0.7 ml/min). Patients also filled out a visual analog scale (VAS) for xerostomia and OHIP‐14 for self‐reported quality of life (QoL). Results: Data showed positive and significant correlation between OHIP‐14 and xerostomia, based on VAS results ( r = 0.52; p = 0.001). Furthermore, there was a negative correlation between UWS and OHIP‐14 scores ( r = −0.34; p = 0.006) and VAS for xerostomia ( r = −0.22; p = 0.09). No significant correlation was found between SWS and OHIP‐14 or VAS neither between DMFT and OHIP‐14. When assessing the level of QoL by the UWS and SWS flow categories a significant association was found for UWS ( p = 0.001) but not for SWS ( p = 0.11). The OHIP‐14 values were higher in the groups with lower salivary flow. The multiple linear regression to predict OHIP‐14 only selected VAS for xerostomia as a statistically significant predictor. Conclusions: Increased level of xerostomia and reduced UWS flow decrease oral health‐related QoL in patients with pSS.